Nanomaterials as an alternative to increase plant resistance to abiotic stresses - Aguirre-Becerra, Humberto; Feregrino-Pérez, Ana Angélica; Esquivel, Karen; Perez-Garcia, Claudia Elena; Vazquez-Hernandez, Ma. Cristina; Mariana-Alvarado, Aurora (Frontiers in Plant Science, 2022)
The efficient use of natural resources without negative repercussions to the environment has encouraged the incursion of nanotechnology to provide viable alternatives in diverse areas, including crop management. Agriculture faces challenges due to the combination of different abiotic stresses where nanotechnology can contribute with promising applications. In this context, several studies report that the application of nanoparticles and nanomaterials positively affects crop productivity through different strategies such as green synthesis of nanoparticles, plant targeted protection through the application of nanoherbicides and nanofungicides, precise and constant supply of nutrients through nanofertilizers, and tolerance to abiotic stress (e.g., low or high temperatures, drought, salinity, low or high light intensities, UV-B, metals in soil) by several mechanisms such as activation of the antioxidant enzyme system that alleviates oxidative stress. Thus, the present review focuses on the benefits of NPs against these type of stress and their possible action mechanisms derived from the interaction between nanoparticles and plants, and their potential application for improving agricultural practices.